A phase conversion method to anchor ZIF-8 onto a PAN nanofiber surface for CO2 capture. Issue 2 (23rd December 2021) - Li, Zeyu; Cao, Zhejian; Grande, Carlos; Zhang, Wenjing; Dou, Yibo; Li, Xiaosen; Fu, Juan; Shezad, Nasir; Akhtar, Farid; Kaiser, Andreas
Abstract : Poly acryl nitrile (PAN) nanofibers were prepared by electrospinning and coated with zeolitic imidazolate framework-8 (ZIF-8) by a phase conversion growth method and investigated for CO2 capture. Abstract : Polyacrylonitrile (PAN) nanofibers were prepared by electrospinning and coated with zeolitic imidazolate framework-8 (ZIF-8) by a phase conversion growth method and investigated for CO2 capture. The PAN nanofibers were pre-treated with NaOH, and further coated with zinc hydroxide, which was subsequently converted into ZIF-8 by the addition of 2-methyl imidazolate. In the resulting flexible ZIF-8/PAN composite nanofibers, ZIF-8 loadings of up to 57 wt% were achieved. Scanning electron microscopy and energy-dispersive X-ray spectroscopy (EDS) showed the formation of evenly distributed submicron-sized ZIF-8 crystals on the surface of the PAN nanofibers with sizes between 20 and 75 nm. X-ray photoelectron spectroscopy (XPS) and carbon-13 nuclear magnetic resonance ( 13 C NMR) investigations indicated electrostatic interactions and hydrogen bonds between the ZIF-8 structure and the PAN nanofiber. The ZIF-8/composite nanofibers showed a high BET surface area of 887 m 2 g −1 . CO2 adsorption isotherms of the ZIF-8/PAN composites revealed gravimetric CO2 uptake capacities of 130 mg g −1 (at 298 K and 40 bar) of the ZIF-8/PAN nanofiber and stable cyclic adsorption performance.